Association of biological age acceleration with all-cause and cardiovascular mortality in HSV-positive adults: A population-based longitudinal cohort study - Jun Wei; Yuefeng Li; Yang Liu (PLoS ONE, 2025)
Background Biological age acceleration reflects physiological aging and its link to mortality in HSV-infected adults is unclear. Methods We analyzed data from 16,065 HSV-seropositive adults aged 20–59 years from the NHANES 1999–2016 cycles (mean age: 35.4 ± 8.5 years). The data were collected in the United States. Biological age acceleration and Phenotypic age acceleration were calculated as residuals from regressing KDM-based biological age and PhenoAge on chronological age, respectively. The mean (SD) values were –10.9 (10.4) and –3.4 (4.6) years. Over a median follow-up of 139 months, 551 all-cause and 131 cardiovascular deaths occurred. Weighted Cox proportional hazards models were used to evaluate associations between biological age acceleration and mortality. Nonlinear associations and potential threshold effects were assessed using smooth curve fitting based on generalized additive models. Subgroup and sensitivity analyses confirmed the robustness of the results. Results Both biological age acceleration and Phenotypic age acceleration were significantly associated with increased all-cause and cardiovascular mortality. Among individuals with Phenotypic age acceleration > –1.8, each 5-year increase was associated with a 68% higher risk of all-cause mortality (HR: 1.68; 95% CI: 1.47–1.92; P < 0.001). For biological age acceleration > 3.14, each 5-year increase was associated with a 16% higher risk (HR: 1.16; 95% CI: 1.03–1.30; P = 0.0133). Results remained consistent across subgroups and in sensitivity analyses. Conclusion In a cohort of HSV-seropositive adults in the United States, biological age acceleration, particularly Phenotypic Age acceleration, was significantly associated with increased risks of all-cause and cardiovascular mortality.